Wood-based Panels Scenario in BRICS Countries - Upadhyay, V. K.; Kamath, Ravikala; Pandey, C. N. (Indian Forester, 2014)
This paper assesses the pattern of wood based panel's production, consumption, import and export during 1991-2010 of BRICS (Brazil, Russia, India, China and South Africa) group of countries. The current scenario shows that BRICS production of wood-based panel is total of 119 million m 3 in 2010. When compared with the world scenario these countries have registered an increase in production from 5.5% to 44.4% and also an increase export quantity from 5.0% to 19.4% during 1991 to 2010. However, there has been decrease in the import quantity from 11.9% to 6.2%.Consumption pattern also indicates that there is an increasing growth from 18.6 million m3 in 1992 to 110.27 million m 3 by 2010. On the basis of the projections made it has been estimated that the BRICS countries will be the highest producer of wood based panels comprising nearly 51.47 per cent of the world output in 2015 and will reach to 54.51 per cent (210.85 million m3 ) by 2020 of global share. Among BRICS countries, share of China is expected to be nearly 45.25 per cent(175.01 million m3) which may be the leading country, Russia is second with 4.13 per cent (15.98 million m3 ) followed by Brazil 3.49 per cent (13.52 million m3), India 1.38 per cent (5.34 million m3) and that of South Africa 0.27 per cent (1 million m3) by 2020 of global share.